Penyajian Laporan Keuangan Syariah dan Non Syariah: Studi Kasus PT. Bank Mandiri dan PT. Bank Mandiri Syariah - Aldi Agung Fidiantoro; Denada Agustia Nanda; Elisa Khoeriyah Sukawanda; Fasa Aska Dera; Ersi Sisdianto (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Standardization of the presentation of accounting information is necessary because many parties (stakeholders) have an interest in the information presented in the company's financial reports. Therefore, the process of presenting financial reports must be based on applicable accounting standards so that the financial information presented provides information that can be understood, relevant, reliable, can be compared in evaluating the financial position and performance of the bank and is useful for users of financial reports (external parties and internal) in economic decision making. Whether conventional (non-shariah) financial institutions or sharia financial institutions, the financial performance of each institution will be visible from the financial reports. Financial reports are media used to conduct research on the health condition of a company consisting of balance sheets, profit and loss calculations, retained earnings and other reports.